2013
DOI: 10.11604/pamj.2013.14.22.1865
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal endoscopy in Nigeria - a prospective two year audit

Abstract: IntroductionGastrointestinal (GI) endoscopy is currently performed by different specialties. Information on GI endoscopy resources in Nigeria is limited. Training, cost, availability and maintenance of equipment are some unique challenges. Despite these challenges, the quality and completion rates are important.MethodsProspective audit of endoscopic procedures by an endoscopist in a Nigerian hospital over a 24 month period.ResultsOne hundred and ninety endoscopic procedures were performed in 187 patients (109 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 22 publications
5
24
0
2
Order By: Relevance
“…This frequency is close to those of other authors [6] [8] [11] [19] who reported results varying between 8.9% and 9.8%. RGO in our study was 1.6 times higher than in Fasla H. [3] and Peghini [20] [12].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This frequency is close to those of other authors [6] [8] [11] [19] who reported results varying between 8.9% and 9.8%. RGO in our study was 1.6 times higher than in Fasla H. [3] and Peghini [20] [12].…”
Section: Discussionsupporting
confidence: 92%
“…This predominance of gastric cancer among cancers of the upper digestive tract is also reported by many authors [4] [22] with prevalence included between 0.92% and 6.7%. Other authors reported rather, a predominance of esophageal cancer [6] [8]. These results show that upper gastrointestinal cancers and stomach cancer are no longer rare in Africa.…”
Section: Discussionsupporting
confidence: 51%
“…Nigeria and other sub-Saharan African countries suggest that they may not be as rare as previously reported though the prevalence rates are still relatively low when compared to the rates reported among Caucasians and Asians [10][11][12][13][14][15][16][17]. Over a period May, 2012 [14].…”
Section: Discussionmentioning
confidence: 99%
“…It was estimated that 30% of the Western population have colonic polyps, whereas lower rates (10-15%) were noted in Africa [8,9]. Recent studies in Nigeria and other sub-Saharan African countries have reported different prevalence rates of colonic polyps that appear to suggest that their occurrence in these countries may not be rare as previously noted [10][11][12][13][14][15][16][17]. Results from previous studies have also shown that colonic polyps are more common in men than in women and increase in frequency with increasing age in most of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, in many countries, physicians who perform GI endoscopy as part of their medical practice are not required to be certified or acknowledged by a regulatory body. [5][6][7][8] Therefore, there is a need for training guidelines which define the minimum duration, procedural skills and competency that should be acquired by physicians during their endoscopy training.…”
Section: Emerging Stars Investigate Standards For Endoscopy Training mentioning
confidence: 99%